Resiliencia y pobreza en el marco de los procesos educativos - Rodríguez Canales, Fredy (2023)
Based on observations in professional performance, teaching and daily interaction with people classified as living in poverty or extreme poverty in Peru, the authors postulate that in the fight to mitigate the deficiencies and unmet needs in which generationally underlying the majority of its inhabitants, human resilience must be understood as the universal, individual or community capacity to overcome adversities and build positively on them. In this phenomenon, they combine affective, social, emotional, spiritual and cognitive competencies, which must be taken into account in the formulation and execution of strategies in public policies, programs and educational systems at all levels, in such a way that these promote psychosocial conditions favorable to resilience, such as: Giving meaning to what one does and is, Good sense of humor, Self-analysis, Autonomy, Cordial and empathetic social interaction, Giving and receiving affection, Positive self-esteem, Identity with positive feelings of belonging, Proactivity, and Creativity.